Homofobia e educação : problematizações e possibilidades de construção de uma cultura de respeito e liberdade às diferenças - Scolari, Adriel Paulo (2014)
The following work examines the homophobia problem and discusses the perspectives and possibilities of constructing, through education, a culture which visualizes and values the differences. Many discussions and current practices still have the homosexuality in a depreciating and prejudice way. When these discussions and practices are found in educational environments, the concern becomes even wider because in these environments next generations individual‟s subjectivities are being formed. If making a solidary world is intended by education, in which all the individuals have a dignified and democratic relationship, it is necessary to worry about an education that creates repugnancy and hate among human beings, for instance, the homophobia. Despite many advances in this aspect, considering the century we are living, the homophobia is a highly present phenomenon in our society, including the Brazilian one, and its repercussion reaches schools. In this dissertation, based on a bibliographic study with hermeneutical approach, it is aimed to analyze the causes for these kinds of behaviors and to evaluate some ideas, which might contribute for the development of a sexual freedom non-discriminating education. Therefore, it is initially described some homophobia practices generated and reproduced in the educational atmosphere and, subsequently based on Michel Foucault e Martha Nussbaum, it is investigated the roots of discussions and sexualities opposed feelings which diverge from the heterosexual pattern, known as natural or normal . From the construction of this pattern, it is also examined how the other ways of living and practicing sexualities were made stigmatized, repulsive, causing exclusion, physical and psychological violence along the years. Based on these considerations, the possibilities and perspectives are pointed out and they can destabilize homophobia in the society, mainly through future generations